IMPLEMENTASI PERMOHONAN KUNJUNGAN ONLINE MELALUI APLIKASI SIMONO DALAM UPAYA TERTIB ADMINISTRASI DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II BANDUNG - Meria Noti Priyanggani; Tiris Sudrartono (Media Bina Ilmiah, 2023)
This study aims to find out how effective the use of this application is to support performance at the Class II Bandung Child Special Development Institute (LPKA), as well as to find out what efforts can improve the performance of using the Simono application to find solutions to these problems. The research method used is a qualitative method. In this study the authors conducted a field study, namely the authors conducted interviews and direct observations with the information and system development section at the Class II Child Special Development Institute (LPKA) Bandung. The results showed that there were problems that arose in the Simono application which often occurred in the system request for an online visit. Advice from the author based on observations, it is best if the Class II Bandung Child Special Development Institute (LPKA) needs to re-evaluate the system in the Simono application whether its use is effective or needs to be improved again, so that its use can function properly and accurately according to the purpose use.